What Is the Long-Term Impact of an Implant Stewardship Program on Orthopaedic Trauma Implant Pricing?. Issue 5 (May 2021) - Morellato, John; O'Hara, Nathan N.; Baker, Mitchell; O'Toole, Robert V.; Pollak, Andrew N.
Abstract : Objectives: To analyze the effectiveness of an implant stewardship program on implant cost containment and to estimate surgeons' responsiveness to implant price changes. Design: Interrupted time series. Setting: Level I trauma center. Patients/Participants: Monitored usage of 5 trauma constructs by 10 surgeons over a 5-year period. Intervention: Red-Yellow-Green (RYG) implant pricing comparison chart. Main Outcome Measurements: Primary outcomes were changes in the mean price, minimum price, and the number of price changes. The secondary outcome was surgeons' responsiveness to RYG/cost changes. Results: The study consisted of 2468 procedures. A mean construct price decrease of 66 per year [95% confidence interval (CI), −170 to −151], with distal femoral plates demonstrating the largest mean annual price decline (486; 95% CI, −540 to −432). The minimum construct price decreased by 131 per year (95% CI, −155 to −111), with the largest reductions observed for distal femoral plates (−436 per year; 95% CI, −516 to −354) and external fixators (−122 per year; 95% CI, −258 to −136). The median price decrease was 407 (range: 6 to 2491) or 12.5% of the previous price. Positive changes in RYG levels increased surgeons' usage of tibial nails by 115%, femoral nails by 106%, and external fixators by 104%. Surgeons' implant selection was insensitive to RYG changes for distal femoral plates [RYG elasticity ( E RYG ): −0.74] and proximal tibia plates ( E RYG : −0.21). Conclusions: The implant stewardship program was associated with substantial implant price reductions. Surgeons' implant selection was especially sensitive to price changes for intramedullary nails and external fixators. Abstract : Supplemental Digital Content is Available in the Text.